1996
DOI: 10.1515/cclm.1996.34.2.125
|View full text |Cite
|
Sign up to set email alerts
|

Conditions for Single Strand Conformation Polymorphism (SSCP) Analysis with Broad Applicability: A Study on the Effects of Acrylamide, Buffer and Glycerol Concentrations in SSCP Analysis of Exons of the p53 Gene

Abstract: We examined the influence of electrophoretic conditions on the detectability of small sequence alterations in DNA fragments by single strand conformation polymorphism (SSCP) analysis. Three acrylamide concentrations, 7.5, 14 and 20%, were selected, and all three gel types were prepared with four different Tris/borate/EDTA buffer concentrations. In addition, all these twelve gels were prepared both with and without 10% glycerol. All electrophoretic runs were performed at ambient temperature of 20-24 °C. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 11 publications
1
13
0
3
Order By: Relevance
“…Some [Glavac and Dean, 1993;Hayashi, 1993] but not all [Ren et al, 1997;Teschauer et al, 1996] studies have demonstrated that glycerol affect the migration profile in a way that increases the sensitivity of SSCP analysis based on slab gel electro-phoresis. Recently, Kukita et al [1997] reported that the effect of glycerol is attributable to reduction of pH of the TBE buffer caused by the reaction of glycerol with borate ion.…”
Section: Ph Of the Separation Matrixmentioning
confidence: 99%
“…Some [Glavac and Dean, 1993;Hayashi, 1993] but not all [Ren et al, 1997;Teschauer et al, 1996] studies have demonstrated that glycerol affect the migration profile in a way that increases the sensitivity of SSCP analysis based on slab gel electro-phoresis. Recently, Kukita et al [1997] reported that the effect of glycerol is attributable to reduction of pH of the TBE buffer caused by the reaction of glycerol with borate ion.…”
Section: Ph Of the Separation Matrixmentioning
confidence: 99%
“…Therefore, we varied the amount of DNA loaded, percentage of formamide used for denaturation, glycerol effect, methods of staining (ethidium bromide and silver nitrate), time and temperature of the electrophoretic run, power applied, and other matrixes as Mutation Detection Enhancement gel solution of Hydrolink (MDE). Such methods for optimizing the method of SSCP have been used in various studies in the literature, e.g., to detect mutations in the p53 gene (21). We also examined the reproducibility of the separation patterns obtained.…”
Section: Resultsmentioning
confidence: 99%
“…. Test buffers of different composition and pH value (e.g., 0.5 Â TBE pH 8.3 or Tris-acetate pH 6.4), if necessary with and without additives such as glycerol (Teschauer et al, 1996). .…”
Section: Electrophoresis Conditions In Native Pagementioning
confidence: 99%